Анализ социальных ситуаций: междисциплинарность, адекватность, информационная полнота - Бородянский, Ю.; Саенко, Ю. (Социология: теория, методы, маркетинг, 2000)
According to the goals and specific character of social reality analysis, there were discussed a series of sociological approaches based on administrative statistics, public opinion polls and expert evaluation. To make a description of social processes, prognoses and recommendations integral and adequate, the authors have suggested to combine various approaches in integral analysis with maximum possible parameters of social situation: regulatives, presentations, intentions of social subjects, their mate -rial well-being and satisfaction, social tension and real behavior.